Mechanical and microstructural behaviour of weldment of two low alloy steels using MIG. (2021) - Kumar, Vijay; Mittal, Manoj; Goyal, Deepam; Goyal, Tarun; Dang, Rajeev Kumar; Bahl, Shashi
Abstract: In industrial applications, various types of materials are used and strength of weldment of two alloys is a major cause of interest among engineering community. In this study P11 and P22 steels were welded using ER −70 - S6 wire electrode with metal inert gas (MIG) welding process using CO2 as shielding gas. The strength of the weldment was tested by impact testing, Hardness by Micro Vicker hardness and Microstructure of weldment before and after the failure was examined using a metallurgical microscope. The results of experiments performed on the specimen on impact testing machine showed that the impact energy of welded specimen was 49 J in Charpy impact test, whereas, that of parent metal P11 was 48 J and for P22, it was 64 J. The result of impact test shows that the impact energy of weldment of P11 and P22 lies between the impact energy of parent alloys. The microhardness at Heat affected zone (HAZ) was highest and at base metal, it was lowest whereas, at weldment microhardness value lies in between microhardness value of base metal and HAZ. Specimen were heat treated in a furnace in an air environment at 700, 800 and 900 °C for 2 h and subsequently cooled in the furnace. The results of impact test show increased strength of weldment after post weld heat treatment (PWHT) at all temperatures however, the strength was found to decrease with increase in temperature of PWHTs.